Immunopathology of Tumefactive Demyelinating Lesions-From Idiopathic to Drug-Related Cases - Vakrakou, Aigli G.; Brinia, Maria-Evgenia; Svolaki, Ioanna; Argyrakos, Theodore; Stefanis, Leonidas; Kilidireas, Constantinos (Frontiers in Neurology, 2022)
Tumefactive demyelinating lesions (TDL) represent a diagnostic dilemma for clinicians, and in rare atypical cases a collaboration of a neuroradiologist, a neurologist, and a neuropathologist is warranted for accurate diagnosis. Recent advances in neuropathology have shown that TDL represent an umbrella under which many different diagnostic entities can be responsible. TDL can emerge not only as part of the spectrum of classic multiple sclerosis (MS) but also can represent an idiopathic monophasic disease, a relapsing disease with recurrent TDL, or could be part of the myelin oligodendrocyte glycoprotein (MOG)- and aquaporin-4 (AQP4)-associated disease. TDL can appear during the MS disease course, and increasingly cases arise showing an association with specific drug interventions. Although TDL share common features with classic MS lesions, they display some unique features, such as extensive and widespread demyelination, massive and intense parenchymal infiltration by macrophages along with lymphocytes (mainly T but also B cells), dystrophic changes in astrocytes, and the presence of Creutzfeldt cells. This article reviews the existent literature regarding the neuropathological findings of tumefactive demyelination in various disease processes to better facilitate the identification of disease signatures. Recent developments in immunopathology of central nervous system disease suggest that specific pathological immune features (type of demyelination, infiltrating cell type distribution, specific astrocyte pathology and complement deposition) can differentiate tumefactive lesions arising as part of MS, MOG-associated disease, and AQP4 antibody-positive neuromyelitis optica spectrum disorder. Lessons from immunopathology will help us not only stratify these lesions in disease entities but also to better organize treatment strategies. Improved advances in tissue biomarkers should pave the way for prompt and accurate diagnosis of TDL leading to better outcomes for patients.